Mechanism of increased clearance of glycated albumin by proximal tubule cells - Wagner, Mark C. (Am J Physiol Renal Physiol, 2016)
Serum albumin is the most abundant plasma protein and has a long half-life due to neonatal Fc receptor (FcRn)-mediated transcytosis by many cell types, including proximal tubule cells of the kidney. Albumin also interacts with, and is modified by, many small and large molecules. Therefore, the focus of the present study was to address the impact of specific known biological albumin modifications on albumin-FcRn binding and cellular handling. Binding at pH 6.0 and 7.4 was performed since FcRn binds albumin strongly at acidic pH and releases it after transcytosis at physiological pH. Equilibrium dissociation constants were measured using microscale thermophoresis. Since studies have shown that glycated albumin is excreted in the urine at a higher rate than unmodified albumin, we studied glucose and methylgloxal modified albumins (21 days). All had reduced affinity to FcRn at pH 6.0, suggesting these albumins would not be returned to the circulation via the transcytotic pathway. To address why modified albumin has reduced affinity, we analyzed the structure of the modified albumins using small-angle X-ray scattering. This analysis showed significant structural changes occurring to albumin with glycation, particularly in the FcRn-binding region, which could explain the reduced affinity to FcRn. These results offer an explanation for enhanced proximal tubule-mediated sorting and clearance of abnormal albumins.